Zircon geochronology suggests a long-living and active magmatic system beneath the Ciomadul volcanic dome field (eastern-central Europe) - Lukács, Reka; Caricchi, L.; Schmitt, Axel Karl; Bachmann, O.; Karakas, O.; Guillong, M.; Molnár, K.; Seghedi, I.; Harangi, Sz. (Earth and planetary science letters, 2021)
Ciomadul is the youngest volcano in eastern-central Europe. Although its last eruption occurred at ca. 30 ka, there are independent indications for a high-crystallinity magma reservoir persisting beneath the volcano until present. In order to further test the hypothesis of long-lived melt presence and to better constrain the nature and timescales associated with the subvolcanic magma storage system, over 500 zircon U-Th and U-Pb spot ages (crystal interiors and outer surfaces) were interpreted from dacitic rocks of the most productive eruptive period (the Young Ciomadul Eruptive Period; YCEP, 160-30 ka). Zircon surface ages from lava dome and pumice samples range from ca. 600 ka up to the youngest eruption event at 30 ka. They form a continuous age distribution and some single crystals reveal significant age zonation (>150 kyr difference from core to rim). The oldest zircon ages of YCEP overlap with the last eruption events of the Old Ciomadul Eruptive Period (1000-330 ka). The zircon age spectra, combined with textural data, point to a prolonged (several 100's kyr) residence in a highly crystalline mush state. The range in zircon crystallization temperature (from ∼750°C to the solidus at ∼680°C) is consistent with the results of thermometry on amphibole and plagioclase from felsic crystal clots, which represent crystal mush fragments. To maintain magma reservoir for such a long time above solidus, continuous magma input by deeper recharge is required. Zircon crystallization model calculations constrained by thermal modelling imply an average rate of magma input of about 1.3 × 10−4 km3/yr over 2 Myr. Such estimate allows us to calculate an extrusive/intrusive ratio of 1:25-1:30. The model calculations suggest that a crystal mush zone of about 35 km3 is still present within the subvolcanic magma reservoir. Importantly, the Ciomadul plumbing system thus remains thermally primed and renewed magma injection could lead to rapid reawakening and eruption of the apparently inactive volcano.
Gesehen am 30.06.2021